The Wnt code: cnidarians signal the way - Guder, Corina; Lengfeld, Tobias; Watanabe, Hiroshi; Holstein, Thomas W. (Oncogene, 2006)
Cnidarians are the simplest metazoans with a nervous system. They are well known for their regeneration capacity, which is based on the restoration of a signalling centre (organizer). Recent work has identified the canonical Wnt pathway in the freshwater polyp Hydra, where it acts in organizer formation and regeneration. Wnt signalling is also essential for cnidarian embryogenesis. In the sea anemone Nematostella vectensis 11 of the 12 known wnt gene subfamilies were identified. Different wnt genes exhibit serial and overlapping expression domains along the oral|[ndash]|aboral axis of the embryo (the |[lsquo]|wnt code|[rsquo]|). This is reminiscent of the hox code (cluster) in bilaterian embryogenesis that is, however, absent in cnidarians. It is proposed that the common ancestor of cnidarians and bilaterians invented a set of wnt genes that patterned the ancient main body axis. Major antagonists of Wnt ligands (e.g. Dkk 1|[sol]|2|[sol]|4) that were previously known only from chordates, are also present in cnidarians and exhibit a similar conserved function. The unexpectedly high level of genetic complexity of wnt genes evolved in early multi-cellular animals about 650|[thinsp]|Myr ago and suggests a radical expansion of the genetic repertoire, concurrent with the evolution of multi-cellularity and the diversification of eumetazoan body plans.
Gesehen am 09.05.2017